Stop and think learning : teacher's guide for motivating children : including those with special needs - Petersen, Lindy. (Australian Council for Educational Research, 1995)
The classroom cocktail. Motivating learning: the ingredients and recipe. Proactive plans: following the recipe. Personal taste: my views on some special needs. Learning and relating: the good mixers.